2019
DOI: 10.3390/metabo9040078
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Microbial Metabolites Exhibit Gut and Blood–Brain Barrier Permeability and Protect Murine Microglia against LPS-Induced Inflammation

Abstract: Increasing evidence supports the beneficial effects of polyphenol-rich diets, including the traditional Mediterranean diet, for the management of cardiovascular disease, obesity and neurodegenerative diseases. However, a common concern when discussing the protective effects of polyphenol-rich diets against diseases is whether these compounds are present in systemic circulation in their intact/parent forms in order to exert their beneficial effects in vivo. Here, we explore two common classes of dietary polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 56 publications
(68 reference statements)
3
47
0
Order By: Relevance
“…Microbial metabolites derived from dietary lignans, a class of polyphenols, like equol and enterolactone, passively cross both the gut and BBB barriers and show protective ability against inflammation in microglia [128]. A recent study demonstrates that microbial polyphenol metabolites could be transported across the BBB endothelium [129].…”
Section: Bioactivity Of Polyphenols and Gut Microbiota Interplaymentioning
confidence: 99%
“…Microbial metabolites derived from dietary lignans, a class of polyphenols, like equol and enterolactone, passively cross both the gut and BBB barriers and show protective ability against inflammation in microglia [128]. A recent study demonstrates that microbial polyphenol metabolites could be transported across the BBB endothelium [129].…”
Section: Bioactivity Of Polyphenols and Gut Microbiota Interplaymentioning
confidence: 99%
“…Studies on dietary polyphenols suggest their beneficial role against Parkinson's disease (PD), which is mainly attributed to antioxidant, anti-inflammatory, and anti-apoptotic activity [1]. The current research trends also cover their metabolic derivatives, in particular, bioavailable gut microbiota metabolites, which offer a novel preventive approach for the disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…All 23 compounds were located in the HIA 99% confidence ellipse, and the absorption grade (Table 1) indicated that all the compounds had good absorption except one, which had moderate absorption. BBB grade predictions indicated that all compounds had medium or very low BBB permeability [24]. Regarding the CYP2D6 inhibition predictions, no compounds inhibited this enzyme and none cause serious drug interaction toxicity.…”
Section: Resultsmentioning
confidence: 99%